(untitled) (Global Journal of Science Frontier Research, 2025)
We have proposed a mechanism that explains all phenomena observed in nature during lightning propagation and all phenomena during the fall of the Chelyabinsk meteorite in the Russian Federation These positively charged cumulative-dissipative plasma systems CDS as we have established are surrounded by incongruent shock waves of the Vysikaylo electric field VSW We demonstrate that de Broglie waves of free electrons arising in the plasma tail behind the meteoroid behave similarly to electromagnetic waves in a laser There a cumulative jet of high-energy electrons CJ is formed which breaks into the meteoroid causing it to collapse according to the Coulomb mechanism The formation of VSW in the atmosphere is due to the peculiarities of the chemical kinetics of negative ions at the boundary of the plasma tail The time of Vysikaylo-Poisson s structural turbulence providing the formation of CJ in the plasma tail was 1 5 s